2010
DOI: 10.1093/jb/mvq074
|View full text |Cite
|
Sign up to set email alerts
|

Diazoxide preconditioning alleviates caspase-dependent and caspase-independent apoptosis induced by anoxia-reoxygenation of PC12 cells

Abstract: Although there is increasing evidence that the ATP sensitive potassium channel (K(ATP)) opener exhibits neuroprotective effects against ischaemic neural damage, little is known about the mechanism. Mitochondria play a key role in apoptosis by releasing many important factors, including cytochrome c and apoptosis-inducing factor, which in turn initiate the caspase-dependent and -independent mitochondrial pathway, respectively. In the present study, we sought to determine the locus that K(ATP) opener uses to med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Theoretically, it is possible that the positive correlation of diazoxide dose and abnormal neurodevelopment indicates that diazoxide itself may be detrimental to the neonatal brain. However, there have been no clinical reports of brain injury from diazoxide use, and there are several studies in animals demonstrating neuroprotective effects of diazoxide (Zhang et al, 2010, Huang et al, 2010). It is possible that diazoxide unresponsiveness represents an independent adverse marker for abnormal neurodevelopment, due to relative drug inactivity at the level of neuronal K ATP channels, which are important for brain neuronal survival.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, it is possible that the positive correlation of diazoxide dose and abnormal neurodevelopment indicates that diazoxide itself may be detrimental to the neonatal brain. However, there have been no clinical reports of brain injury from diazoxide use, and there are several studies in animals demonstrating neuroprotective effects of diazoxide (Zhang et al, 2010, Huang et al, 2010). It is possible that diazoxide unresponsiveness represents an independent adverse marker for abnormal neurodevelopment, due to relative drug inactivity at the level of neuronal K ATP channels, which are important for brain neuronal survival.…”
Section: Discussionmentioning
confidence: 99%
“…Opening of K ATP channels has been shown to be a prerequisite event for the induction of protection against ischemia–reperfusion injury by RIPC, IPost, and RIPost (Schmidt et al , 2007; Steensrud et al , 2010; Yang et al , 2004). Zhang et al (2010) used an in-vitro model of PC12 cells undergoing oxygen glucose deprivation to reveal that activation of K ATP channels elicits protective effects against oxygen glucose deprivation-induced cell apoptosis by caspase-dependent and -independent mitochondrial pathways. In addition, Loukogeorgakis et al (2007) revealed that transient limb ischemia induces RIPost in humans by a K ATP channel-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The organic osmolytes stabilize intracellular proteins (Burg et al 2007; Lang & Hoffmann, 2012). The stabilisation of the permeability transition pore by organic osmolytes counteracts mitochondrial depolarization (Zhang et al 2010). The protein stabilisation contributes to the inhibitory effect of organic osmolytes on apoptotic cell death (Burg et al 2007; Zhang et al 2010).…”
mentioning
confidence: 99%